The impact of the ERCC2 Lys751Gln polymorphism on the risk of acute myeloid leukemia in an Iraqi patients - Mouhi Jasiem, Thamer; Al-Hussaini, Rand Muhammed Abdul-Hussain (Journal of Contemporary Medical Sciences, 2023)
Objectives: AML is the only type of acute leukemia diagnosed in adults and is less common in children. It has the lowest survival rate. This study aimed to investigate the epidemiological risk factors for AML expansion comprise environmental factors, for instance, smoking , and therapy-related factors. Methods :The study was conducted on 70 acute myeloid leukemia patients—37 females and 33 males and on 30 healthy people—12 females and 18 males—as a control group. DNA was extracted from the study groups' whole blood samples using the gSYNCTM DNA Extraction Kit. The T751G polymorphism of the ERCC2 gene was determined by the PCR-RFLP technique. Results: In genetic analysis, it was shown that the carriers of allele Lys and genotype Lys/Lys have a lower risk of developing AML, while allele carriers Gln have an increased risk. The results showed the ERCC2 gene, Lys 751 Gln (T/G) heterozygous TG genotypes, and the G allele were significantly higher (P<0.05) in AML patients compared to the control group. In the sequencing of the region we studied, it was found that there is a site of diversity that is located between the CTTCAG and CTGCAG, where a change in nucleotides (T to G) represents the restriction site of the restriction enzyme. Conclusion : The polymorphic marker 751 Gln> Lys of the ERCC2 gene was associated with the development of AML in Iraqi patients. It was discovered that allele Lys genotype Lys/Lys carriers have a lower risk of developing AML, whereas allele Gln carriers have an increased risk.